EXPERIMENTAL STUDY ON ACCOUNTING STUDENTS: PERSUASION ELABORATION MODEL IN ETHICAL DECISION LEARNING - Wulanditya, Putri (Universitas PGRI Madiun, 2024)
ABSTRACT This research aims to test students' understanding of fraud cases using the persuasion elaboration model, namely the influence of argument framing, source credibility, and emotional condition on the decision to reveal fraud. This research method uses a 2x2x2 online laboratory experiment between subjects with 127 accounting students from Universitas Hayam Wuruk Perbanas. The results showed that the argument framing (positive vs. negative) did not make a significant difference. In contrast, source credibility (high vs. low) and emotional condition (good vs. bad) made a significant difference in accounting students' decisions to reveal fraud. This research contributes to behavioral accounting theory developed with communication science in predicting the behavior of prospective accountants. ABSTRAK Penelitian ini bertujuan untuk menguji pemahaman mahasiswa atas kasus kecurangan menggunakan model elaborasi persuasi, yaitu pengaruh pembingkaian argumen, kredibilitas sumber, dan kondisi emosi terhadap keputusan mengungkapkan kecurangan. Metode penelitian ini menggunakan eksperimen laboratorium online antar subjek 2x2x2 dengan partisipan sebanyak 127 mahasiswa akuntansi Universitas Hayam Wuruk Perbanas. Hasil penelitian menunjukkan bahwa pembingkaian argumen (positif vs negatif) tidak memberikan perbedaan yang signifikan, sedangkan kredibilitas sumber (tinggi vs. rendah), dan kondisi emosi (baik vs. buruk) memberikan perbedaan yang signifikan dalam keputusan mahasiswa akuntansi mengungkapkan kecurangan. Penelitian ini berkontribusi pada teori akuntansi keperilakuan yang dikembangkan dengan ilmu komunikasi dalam memprediksi perilaku calon akuntan.